2014
DOI: 10.3892/mmr.2014.2964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term soft contact lens wear on the corneal thickness and corneal epithelial thickness of myopic subjects

Abstract: To perform safe and successful corneal refractive surgery on myopic patients, corneal thickness (CT) and corneal epithelial thickness (CET) must be accurately measured. Numerous individuals with myopia wear soft contact lenses (SCLs) for the correction of visual acuity but may subsequently undergo corneal refractive surgery. The aim of the present study was therefore to investigate the effects of long-term SCL wear on the CT and the CET of myopic subjects in order to guarantee the safety and accuracy of subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 35 publications
1
30
1
1
Order By: Relevance
“…[198][199][200][201][202][203][204][205] Transient subclinical stromal edema frequently occurs, and corneal thinning of the epithelium and stroma during contact lens wear has also been reported. 203,[206][207][208] Endothelial changes can occur, including polymegethism, pleomorphism, and, rarely, reduction of endothelial cell density. [209][210][211] The clinical significance of transient edema, thinning, and endothelial changes is uncertain.…”
Section: Complicationsmentioning
confidence: 99%
“…[198][199][200][201][202][203][204][205] Transient subclinical stromal edema frequently occurs, and corneal thinning of the epithelium and stroma during contact lens wear has also been reported. 203,[206][207][208] Endothelial changes can occur, including polymegethism, pleomorphism, and, rarely, reduction of endothelial cell density. [209][210][211] The clinical significance of transient edema, thinning, and endothelial changes is uncertain.…”
Section: Complicationsmentioning
confidence: 99%
“…Several methods have been introduced to measure CET, such as confocal microscopy 13 14 , optical pachymetry 15 , optical coherence tomography (OCT) 16 17 , high frequency ultrasound biomicroscopy 8 , and very high frequency digital ultrasound 18 . Fourier-domain optical coherence tomography (FD-OCT) is a high-speed, high-resolution, non-contact, 3-dimensional OCT, which has been applied in measuring CET for patients with keratoconus, corneal ectasia and dry eye, patients undergoing LASIK surgery, patients wearing soft or hard contact lenses and normal patients with relatively high repeatability 6 12 19 20 21 22 23 24 . This study presented CET maps of the central (2-mm diameter area), para-central (2- to 5-mm diameter area) and peripheral (6-mm diameter area) corneas in normal Chinese school children using FD-OCT.…”
mentioning
confidence: 99%
“…The literature is controversial about whether age, gender, or refractive errors affect the corneal ET. [4][5][6][7] Several studies [8,14,17] showed a signi cant decrease in ET among CL-wear groups, with and an increase in thickness following discontinuation of the soft contact lenses. [8] It is important to note that our group of patients, seeking refractive surgery, were mostly young adults with varying degrees of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…[1,3] Several factors have been shown to in uence the central epithelial thickness pro le, and while controversial in the literature, they include age, [4,5] gender, [4,6] ethnics and refractive errors. [6,7] Pathological conditions, such as contact lens (CL) wearing, [8] dry eye, [9,10] and keratoconus, [11] have been also shown to cause alterations of ET.…”
Section: Introductionmentioning
confidence: 99%